Pengaruh Jenis Kelamin, Usia, Tingkat Pendidikan, dan Golongan Terhadap Disiplin Pegawai Negeri Sipil Bagian Umum Kantor Sekretariat Daerah Kabupaten Bengkayang - Sutarman 01 (Universitas Muhammadiyah Pontianak, 2014)
This study aimed to examine the extent to which the relationship variables (gender, age, level of education and class) to the discipline of civil servants in the General Section of the Regional Secretariat Bengkayang, to analyze the factors that have a positive and significant relationship with the discipline in General District Secretariat Office Bengkayang. The sample in this study population using all Civil Servants in the General Section Regional Secretariat Bengkayang of 60 people (saturated sampling technique). The analytical method used was a bivariate analysis with chi square test (χ2) and the hypothesis testing. Based on the analysis results of the chi square test showed that four factors have a positive and significant relationship with the discipline of civil servants, namely Gender, the value of χ2 count = 6173> Asymp. sig. (1-sided) = 0.013. Age to calculate χ2 = 23.741> Asymp.Sig. (1-sided) = 0.000. Education level with χ2 count = 11 507> Asymp.Sig. (1-sided) = 0.009. and a group with a value of χ2 count = 10 446> Asymp. sig. (1-sided) = 0.005.